MUTU BIJI KAKAO LINDAK PADA BERBAGAI LAMA WAKTU FERMENTASI - Nursalam, Nursalam (FAPETKAN UNTAD, 2005)
The purposes of the research were to know the quality of cacao bulk on various time depth of fermentation. It was done in Rahmat of Palolo Sub-District, Donggala District. The Research was set up in Randomized Block Design with 6 treatments and 3 replications. The treatments were ; (L0) without fermentation, (L1) 2 days, (L2) 4 days, (L3) 6 days, (L4) 8 days and (L5) 10 days fermentation time depth. The Result indicated that treatment fermentation time depth had effect on quality of kakao bulk and 6 days fermentation showed the best result from all of the treatments. Even thought on the statistic, that treatment had little differ with 8 days fermentation. Key words: Quality, cacao, fermentation, time depth